Khazanah Folklor untuk Menumbuhkan Karakter Empati dan Cinta Kasih - Murdianto Murdianto (Study Program of Arabic Language Teaching, 2020)
Indonesia is rich in folklore treasures, in the form of traditional stories, proverbs, guesses, poetry, and humour. Folklore can be adapted in the process of growing student character in learning sessions or other activities. This study seeks to uncover how the use of folklore in developing the character of empathy and love for children. This research is a metacognition study. This qualitative study is oriented towards the conceptual exploration of various literary works, research on mapping the views of experts, and about the folklore and character education. This paper shows that folklore is recommended for use in the form of storytelling, role-playing, even for counselling purposes.